Use of continuous glucose monitoring and its association with type 1 diabetes control in children over the first 3 years of reimbursement approval: Population data from the ČENDA registry - Šumník, Zdeněk; Pavlíková, Markéta; Pomahačová, Renata; Venháčová, Petra; Petruželková, Lenka; Škvor, Jaroslav; Neumann, David; Vosáhlo, Jan; Konečná, Petra; Čížek, Jindřich; Strnadel, Jiří; Průhová, Štěpánka; et al. (Pediatric diabetes, 2021)
OBJECTIVE: Increased access to modern technologies is not always accompanied by a decrease in HbA1c. The aim of this study was to identify changes in the proportion of continuous glucose monitoring (CGM) users since 2017, when general reimbursement for CGM became effective in Czechia, and to test whether HbA1c is associated with the percentage of time spent on CGM. RESEARCH DESIGN AND METHODS: All T1D children in the Czech national ČENDA registry (3197 children) were categorized according to their time spent on CGM and associations with age, sex, center size, and HbA1c were tested with calendar year as a stratification factor. RESULTS: The proportion of children with any CGM use increased from 37.9% in 2017 to 50.3% in 2018 and 74.8% in 2019. Of the CGM users, 16%, 28%, and 41% of the children spent >70% of their time on CGM over the 3 years of the study period, with an overrepresentation of children in the <10 years age group versus the older age groups (p < 0.001). The proportion of CGM users differed among centers and was positively associated with a large center size (>100 patients) (p < 0.001). HbA1c was negatively associated with the time spent on CGM (p < 0.001). CONCLUSIONS: A rapid increase in CGM use was reported over the 3 years after general reimbursement. HbA1c was associated with time spent on CGM, a continuing decrease was observed in the >70% category. Reimbursement for CGM likely contributes to the improvement of T1D control at the population level.
Keywords: Insulin; type 1 diabetes; diabetes mellitus 1. typu; Male; Child, Preschool; registry; inzulin; selfmonitoring glykemie; glykovaný hemoglobin; Adolescent; sexuální faktory; Česká republika; Child; Infant; Insurance, Health, Reimbursement; dítě; Age Factors; Blood Glucose Self-Monitoring; mužské pohlaví; CGM; registrace; mladiství; Czech Republic; Time Factors; předškolní dítě; hypoglykemika; lidé; ženské pohlaví; Glycated Hemoglobin; Humans; Sex Factors; kojenec; časové faktory; věkové faktory; Hypoglycemic Agents; Glycated Hemoglobin A; Diabetes Mellitus, Type 1; Registries; úhrada zdravotního pojištění; Female; children